2005
DOI: 10.1095/biolreprod.104.031583
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Phthalates on the Testis and the Liver1

Abstract: Phthalates have been shown to elicit contrasting effects on the testis and the liver, causing testicular degeneration and promoting abnormal hepatocyte proliferation and carcinogenesis. In the present study, we compared the effects of phthalates on testicular and liver cells to better understand the mechanisms by which phthalates cause testicular degeneration. In vivo treatment of rats with di-(2-ethylhexyl) phthalate (DEHP) caused a threefold increase of germ cell apoptosis in the testis, whereas apoptosis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 50 publications
3
53
0
1
Order By: Relevance
“…In the testis, the three PPAR isoforms are expressed in both somatic and germ cells (Braissant et al 1996, Elbrecht et al 1996, Bhattacharya et al 2005. PPAR and PPAR / are widely expressed in interstitial Leydig cells and seminiferous tubule cells (Sertoli and germ cells) (Braissant et al 1996, Schultz et al 1999.…”
Section: Testismentioning
confidence: 99%
See 1 more Smart Citation
“…In the testis, the three PPAR isoforms are expressed in both somatic and germ cells (Braissant et al 1996, Elbrecht et al 1996, Bhattacharya et al 2005. PPAR and PPAR / are widely expressed in interstitial Leydig cells and seminiferous tubule cells (Sertoli and germ cells) (Braissant et al 1996, Schultz et al 1999.…”
Section: Testismentioning
confidence: 99%
“…Indeed, PPAR -and PPAR / -null mice are viable and fertile (Lee et al 1995, Peters et al 2000. Xenobiotic ligands of PPAR and PPAR induce the translocation of these receptors to the nucleus of Sertoli cells (Bhattacharya et al 2005). PPAR is also more strongly expressed in human testicular cancer cells than in normal testicular tissues.…”
Section: Testismentioning
confidence: 99%
“…In this regard, it has been shown that stress signals are related to an increase in ROS production, along with an activation of the p38MAPK pathway (Liu and Chang, 2009) that in turn upregulates the Fas/FasL system. However, EDs promote inactivation of p38MAPK and ERK1/2 in isolated Sertoli cells and TM4 cells (Aravindakshan and Cyr, 2005;Bhattacharya et al, 2005), which has been related to the downregulation of TJ, AJ and GJ proteins and in this way induces sloughing and apoptosis of germ cells, showing that the mechanisms of ED affects spermatogenesis are still a subject of controversy.…”
Section: A Molecular Model Of Eds In Mammalian Testesmentioning
confidence: 99%
“…Phthalates are a class of widely used industrial compounds known technically as di-alkyl or alkyl aryl esters of 1,2-benzenedicarboxylic acid and are used mainly as a specialty plasticizer for nitrocellulose, polyvinyl acetate, and polyvinyl chloride, a lubricant for aerosol valves, an antifoaming agent, a skin emollient, and plasticizer in nail polish, fingernail elongates, and hair spray (1,2). There are many phthalates with many uses, and just as many toxicological properties.…”
Section: Introductionmentioning
confidence: 99%